Mumps treatment by quacks in Pakistan: A neglected danger to public health - Mustafa, Areeba; Rasool, Faiz; Samdani, Khubaib (Journal of the Pakistan Medical Association, 2024)
Dear Editor, In this letter, we aim to draw attention to mumps treatment through pseudo therapies by quacks in Pakistan. Our goal is to raise awareness and promote the prevention of mistreatment. Pakistan has seen an unprecedented rise in mumps outbreaks after the COVID-19 pandemic. From 1 January to 31 December 2022, a total of 19,444 mumps cases had been recorded from all provinces of the country. [1] Mumps is a common childhood respiratory infection caused by a paramyxovirus. It can be transmitted through direct contact and droplet spread. Symptoms include swelling of the parotid gland, which occurs in 60-70% of infections and 95% of patients with symptoms. [2] The swelling progresses over 2-3 days and persists for about a week. Sometimes mumps can lead to later complications such as epididymal-orchitis, oophoritis, meningitis, encephalitis, thyroiditis, unilateral deafness, spontaneous abortion, pancreatitis or infertility. Mumps is benign, resolving on its own, requiring only symptomatic relief by proven medical therapies. [3] Unfortunately, in Pakistan, especially in rural areas, people seek pseudo therapies for various diseases including Mumps from quacks which are found in a significant number of over 600,000 in the country. [4] The harmful effects of such malpractices include abandonment and delays in effective medical treatment, emergence of complications, psychological-physical traumas, and financial burden. [5] For treating Mumps, these mal practitioners offer the "massage" of the parotid gland, which involves rotating the index finger from the centre of the gland towards the outside while blowing on the patient's face. [6] These methods are not scientifically proven and may even be harmful. According to a study, non-medical interventions like acupuncture have also proved to be futile and of no advantage. [7] People often attribute the recovery to the quack's treatment, increasing their trust in these practitioners and propagation of false beliefs. These quacks often charge significant amounts of money, further exploiting their patients. We urge physicians, public health workers and the general public to prioritise the prevention and control of mumps outbreaks. This will require proactive education to address the misinformation surrounding mumps and quack treatments. Furthermore, research is needed to determine the frequency of mumps complications later in life, which may be associated with these ongoing practices for many years. Finally, the government should take stern action against quack practitioners, and the public needs to be better informed about the harms. ---Continue